Mental Health Impacts of Quarantine: Insights from the COVID-19 International Border Surveillance Study in Toronto, Canada - C. Regehr; V. Goel; E. De Prophetis; M. Jamil; D. Mertz; L. Rosella; D. Bulir; M. Smieja (European Psychiatry, 2022)
Introduction Nations thorughout the world are imposing mandatory quarantine on those entering the country. While such measures may be effective in reducing the importation of COVID-19, the mental health implications remain unclear.